Pengaruh Pendapatan dan Gaya Hidup Terhadap Perilaku Konsumtif Masyarakat Kecamatan Tahuna - Gaghana, Lidia; Rumagit, Merry C. N. (Jurnal Equilibrium, 2023)
This study aims to determine the effect of income and lifestyle on the consumptive behavior of the Tahuna sub-district community. This research method is a survey method with a sample of 30 people. The technique used in data collection is a questionnaire technique (questionnaire), observation and documentation. The results of the study were analyzed using multiple linear regression analysis methods, and simple correlation analysis and multiple correlation analysis. The results of this study indicate: (1) Income has a positive and significant effect on the consumptive behavior of the Tahuna sub-district community by 58.5% with a total tcount > ttable = 6.266 > 1.697 (2) Lifestyle has a positive and significant impact on the consumptive behavior of the Tahuna sub-district community. by 71.2% with the number of tcount > ttable = 8,305 > 1,697 (3) Income and Lifestyle have a positive and significant effect on the Consumptive Behavior of the Tahuna subdistrict community by 61.4% with the number of fcount > ftable = 53,375 > 3.35. Keywords: Income, Lifestyle and Consumptive Behavior